A Review of Transition Metal Dichalcogenides-Based Biosensors - Sun, Hongyu; Li, Dujuan; Yue, Xiaojie; Hong, Rui; Yang, Weihuang; Liu, Chaoran; Xu, Hong; Lu, Jun; Dong, Linxi; Wang, Gaofeng; Li, Dongyang (Frontiers in Bioengineering and Biotechnology, 2022)
Transition metal dichalcogenides (TMDCs) are widely used in biosensing applications due to their excellent physical and chemical properties. Due to the properties of biomaterial targets, the biggest challenge that biosensors face now is how to improve the sensitivity and stability. A lot of materials had been used to enhance the target signal. Among them, TMDCs show excellent performance in enhancing biosensing signals because of their metallic and semi-conducting electrical capabilities, tunable band gap, large specific surface area and so on. Here, we review different functionalization methods and research progress of TMDCs-based biosensors. The modification methods of TMDCs for biosensor fabrication mainly include two strategies: non-covalent and covalent interaction. The article summarizes the advantages and disadvantages of different modification strategies and their effects on biosensing performance. The authors present the challenges and issues that TMDCs need to be addressed in biosensor applications. Finally, the review expresses the positive application prospects of TMDCs-based biosensors in the future.